Pengaruh Pemakaian Karbamid Peroksida 10% sebagai Pemutih pada Perokok terhadap Perubahan Gemma gustatoria dan Ketebalan Epitel Lidah (Kajian Histologis pada Rattus Norvegicus): The, Influence of Carbamide Peroxide10% as - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Whitening tooth is used to treat discoloured teeth by strong oxidizing agent. The use of tooth whitening agent may cause a harmful effect i.e. causing tongue mucosa disorder that exposed by carsinogenic agent such as cigarette smoke. Gemma gustatoria are primary chemoreceptors for taste perception. They might undergo changes because of cigarette smoking and carbamide peroxide exposure which eventually lead to taste disorder. The research is aimed to determine the influence of carbamide peroxide10% as tooth whitener on smokers on the changes of gemma gustatoria and thickness of epitelial tongue. Twenty white rats were divided into 4 groups containing of 1 control group and 3 treatment groups. Group A was not treated at all, Group B was exposed by cigarette smoke, Group C was given carbamide peroxide 10%, Group D was exposed by cigarette smoke with carbamide peroxide 10%. Histological evaluation was done by Haematoxyline-Eosin staining and exposed by microscope and visopan to enumerate and measure the cell amount and diameter of gemma gustatoria as well as the thickness of epithelium. The data were analyzed by one-way analysis of variance (ANOVA). The results showed that there was a significant difference (p